Factor affecting Malaysia palm oil demand in United State / Mohd Shahrom Sha’ari and Nur Amalina Ismail - Sha’ari, Mohd Shahrom; Ismail, Nur Amalina (Faculty of Plantation and Agrotechnology, 2018)
Palm oil is one of the agricultural products in Malaysia that provide a lot of potential in the economic growth. Malaysia had been one of the major producer and exporter of palm oil. The demand of palm oil had increase year by year. The objective of this study is to identify the factor that influences Malaysia palm oil demand in United State and also to investigate the relationship between demand and the production of palm oil. In order to conduct this study; secondary data (time series) was used which is annually data from 1986 until 2016 was collected to be analyses. The dependent variable of this research is consumption of palm oil represent the demand on palm oil while population, palm oil price and soybean price as independent variable. This study also test whether there have been long run relationship between demand palm oil with among the all variable above. The Phillips Perron and Augmented Dickey' Fuller test reveals mostly the data was stationary' at first difference except on population data. The Johension co-integration test show' that population and soybean price are positive significant while the palm oil price have negative relationship towards demand on palm oil and all the variable are significant at one per cent level significance. In short run, the result reveals that only palm oil price has not significant effect on palm oil demand. Therefore, the government should support palm oil industry to grab this opportunities of the high demand palm oil to fulfil the demand by increase the production of palm oil and also to find the new alternative to enhance the production through make the research continuously.